PENINGKATAN KAPASITAS SDM PERTANIAN ; POLA KOMUNIKASI PEMBANGUNAN MASYARAKAT UNTUK PEMANFAATAN INTERNET - Mahirawan Setiadhi (Universitas Tidar, 2020)
Internet comes with a new possibilities, for agriculture, it can create a new stream of information about anything, whether it is about price of the crops, weather forecast, or in the next level, sharing and talking about innovation. Hence, despite the benefit of the internet, many of agricultural people didn’t make use of it to the fullest. This occur not just because their lack of knowledge about the internet itself, but also their lack capacity to know what best and what do they need about using the internet for their agriculuture. This research using literature review comunication in development paradigm modernization (top down) and alternative (bottom up) with descriptive methods. The result in this article reveal both of the paradigms can be used in certain condition depends of the capacity of agricultural people that involved in. In modernization paradigm, must include inisiator to boost people knowledge for internet, but in alternative paradigm, the inisiator didn’t have to much involve. So whether both of these type development communication used, it all depends on the capacity of the agricultural people on percieving the problems, or in this case the internet.. Keywords: Development, Communication, Internet, Agriculture, Agricultural Development